Understanding Michael Porter : the essential guide to competition and strategy - Magretta, Joan, 1948- (Boston, Mass. : Harvard Business Review Press, 2012)
Examines and explains the revolutionary business frameworks of Michael Porter, with examples to illustrate and update Porter's ideas for achieving and sustaining competitive success.
Competition: the right mind-set -- The five forces: competing for profits -- Competitive advantage: the value chain and your P&L -- Creating value: the core -- Trade-offs: the linchpin -- Fit: the amplifier -- Continuity: the enabler -- Epilogue: a short list of implications.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Porter, Michael E., -- 1947-; Porter, Michael E., -- 1947-; Porter, Michael E. / 1947-; Porter, Michael E., -- 1947-; Competition; Strategic planning; Management; Strategisches Management; Wettbewerb; Competition; Strategic planning; Management; Strategisches Management; Wettbewerb; Competition; Management; Strategic planning; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books